Pemberian Pakan Suplemen Selama Kebuntingan pada Induk Kambing Etawa - Murniati, Tati; Muchlis, Ahmad (Jurnal Ilmu dan Teknologi Peternakan Terpadu, 2021)
Nutritional improvement in goats can be done by regulating the provision of rations during goat mother's pregnancy in utero conditions that can affect fetal growth. Adequate supply of nutrients during goat mother's pregnancy is a major factor in the internal environment of the unborn child, which is expected to have an impact on better performance for the next life. In addition to being given a basal ration based on the treatment, the mother goats were given supplementary feed. Supplementary feed in the form of Urea molasses multinutrient block (UMMB) provided as much as 100-150 g/head/day. All pregnant goats were grouped according to gestational age and given supplementary feed according to the length of gestational age status. Supplementary feed given to pregnant goat contained different levels of crude protein (PK), 23.75%, 25.26% and 27.16%. Pregnant goat without supplementation of feed during pregnancy, goat mothers aged 1 to 2 months of pregnancy were given supplementary feed (first trimester). Parent aged 3 to 5 months of gestation were given supplementary feed (third trimester). pregnant goat mothers are given supplementary feed during pregnancy. The results of the study that different levels of protein supplement feed had an effect on dry matter consumption of the ration, the highest consumption was in the third trimester of pregnancy (gestational age of 3 to 5 months). Supplementary feeding during pregnancy resulted in high maternal weight gain. The level of digestibility of the feed in vivo, the highest crude protein digestibility level was in the supplementary feed containing 23.75% crude protein.